RUP Based Analysis and Design with Aspects - Cole, Leonardo; Piveta, Eduardo Kessler; Sampaio, Augusto (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2004)
Aspect-Oriented Software Development (AOSD) is a new paradigm aiming to solve problems that are not adequately addressed by the Object-Oriented paradigm. Therefore, it seems appropriate to adapt software processes showing when and how crosscutting concerns should be considered. The Rational Unified Process (RUP) is one of the most widely used software development processes focusing on object-oriented software development, but RUP was not originally conceived considering separation of crosscutting concerns. This work proposes adjustments to one of the most affected RUP disciplines, Analysis and Design, in order to use new concepts and techniques of AOSD. A case study is developed to validate the proposed approach.